Instagram Sexualization: When posts make you feel dissatisfied and wanting to change your body. (December 2021) - Guizzo, Francesca; Canale, Natale; Fasoli, Fabio
Highlights: Sexualized female pictures posted on Instagram lead to greater body dissatisfaction. Appearance comments have no effect on body dissatisfaction. Instagram addiction predicts greater cosmetic surgery intentions. Instagram addiction moderates the condition's effects on cosmetic surgery intentions. Abstract: Instagram is a visually centered social media that involves the presence of sexualized imagery posted by users. Such Instagram sexualization may have a negative impact on women's body image. The present study examined whether exposure to Instagram sexualization, namely posts of sexualized women along with appearance-related comments, affected women's body satisfaction and cosmetic surgery intentions. In doing so, it also considered the moderating role of Instagram Addiction Proclivity (IAP). Young Italian female participants ( N = 247) were randomly exposed to one of four video conditions resulting from the combination of either sexualized or non-sexualized women's pictures on Instagram, paired with appearance or neutral comments. In the sexualized picture condition participants' body dissatisfaction increased compared to pre-exposure levels and to the non-sexualized picture condition. The type of comments did not affect participants' body satisfaction. Moreover, IAP predicted cosmetic surgery intentions and moderated their reactions to Instagram content. Indeed, the higher the IAP, the higher the cosmetic surgery intentions of participants viewing sexualized pictures with neutral comments and non-sexualized pictures with body appearance comments. These findings suggest that female Instagram users should be aware of the negative impacts of viewing sexualized imagery as well as the role that IAP may play.